Sindhenan Banyumasan - Muriah Budiarti (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2008)
Sindhenan is a vocal material in which many elements must be processed and translated in to musical’s language, the elements are songs and texts. In the Gendhings’ Banyumasan ‘s Sindhenan there are two groups call Sindhenan Umum and Sindhenan Khusus. Sindhenan in Banyumas’ gendings have an relationship elements, first in text elements called wangsalan, abon-abon/isen-isen, parikan, senggakan, macapat, sekar ageng, sekar tengahan and sekar bebas. And the second is song’s elements, there are irama, laras, cengkok, and pathel. in the Banyumas’ art workers usually found the term to call garap technique which have Banyumas ‘style, and for the Surakarta and Yogyakarta’s style call garap wetanan, and Sundanesse style call kulonan  Keyword : Sindhenan and the elements which is to build sindhenan